(untitled) (Research, Society and Development, 2020)
In the absence of specific recommendation of nitrogen fertilization and application management for BRS 358 with special type of grain oriented Japanese cuisine. Objective was to determine the best dose and nitrogen application management in coverage for BRS 358, conducted in lowland Roraima that will provide greater agronomic and economic efficiency. Thus, it was an experiment conducted in Roraima lowland area in the municipality of Cornwall, in Gleysol Hápico tb dystrophic. The experimental design was a randomized block in split plot design (4x4), with four repetitions, totaling 64 sample units. The factor doses was allocated in the plots (50 kg ha-1, 100 kg ha-1, 150 kg ha-1, 300 kg ha-1) and the second factor managements of nitrogen application in the subplots: M1: 50% on base and 50% at 45 days after emergence (DAE); M2: 100% application at 15 DAE; M3: 25% at the base and 75% in coverage divided into ½ to 15 ½ and 45 DAE; M4: 25% base; 25% at 15 DAE; 25% at 35 DAE and 25% to 55 DAE. We evaluated the rice crop production components as the methodology recommended by the Standard Evaluation System For Rice. The results show the influence of the nitrogen dose and application management on yield components evaluated, where the features were highly correlated, resulting in maximum productivity physical efficiency of 6.245 kg ha-1, maximum economic efficiency of 6.193 kg ha-1 with Application of 209 to 182 kg ha-1 of urea, respectively. Although application of 25% at the base and 75% in coverage divided into ½ to 15 ½ and 45 DAE (M3) have provided better performance of production components, application of N, 50% at the base and 50% at 45 DAE, promoted largest increase in grain yield in shell, being considered the most promising management for BRS 358.